Optimizing Demonstration Security to Prevent Anarchic Actions by Demonstrators in Order to Create a Conducive Public Order in the Balikpapan Police Area - Muhammad Harits Arlianto (Advances in Police Science Research Journal, 2021)
Optimizing Demonstration Security to Prevent Anarchic Actions by Demonstrators The background of this writing lies in securing the Omnibus Law in Balikpapan. Based on the analysis and security assessment of the integrated omnibus law demo by the Balikpapan Police Dalmas unit, it appears that the Dalmas unit cannot guarantee the stability of the situation and tends to rely too much on the BKO Satbrimobda. . The conclusion that can be drawn is that it is still necessary to analyze and evaluate the performance of security demonstrations at the Balikpapan Police Station. The purpose of this research is to explain the security of demonstrations, efforts to prevent anarchic actions and efforts to create a conducive public order at the Balikpapan Police. The theory used is the theory of Mass Psychology, the concept of demonstrations, the concept of empowerment, the concept of social control, and several related Perkap, the author is guided by the Perkap 1 of 2009 and Perkap 16 of 2016, and its relation to efforts to prevent anarchic action, the study of the concept of empowerment is used. and social control, while for efforts to create a conducive social order, the author uses the study of mass psychology theory to discuss it. The approach taken by the researcher is a qualitative approach and field research methods. Researchers of course can find out the real picture by means of field studies, interviews and document review. The conclusion from the author in analyzing the existing data is that the Balikpapan Police Station is still not optimal in securing demonstrations because there are still some shortcomings. The problem lies in human resources so that improvements can be made based on the concept of empowerment. In order to create a conducive situation and conditions within the kamtibmas itself, there must be a collaborative effort between the community and the police. The author recommends the Balikpapan Police at the time of implementation in the field to continue to coordinate with the korlap who staged the demonstration in order to keep it under control and create good integration between the apparatus and the community, then to prevent this anarchic action the Polresta must be able to fulfill the 3 aspects above. A conducive Kamtibmas in the Legal Area of ​​the Balikpapan Police.